2014
DOI: 10.1016/j.transproceed.2013.08.111
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Living Versus Deceased Donor Liver Transplantation for Acute Liver Failure in the United States

Abstract: Clinical outcomes for living donor liver transplantation (LDLT) for acute liver failure (ALF) in the United States remain to be determined. To address this gap in knowledge, we examined post–liver transplantation outcomes of adults with ALF undergoing LDLT and deceased donor liver transplantation (DDLT) in the United States. We analyzed Organ and Procurement and Transplantation Network data for adults with ALF who were listed for liver transplantation as status 1 or 1A and who underwent LDLT (N = 21) or DDLT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
1
8
2
Order By: Relevance
“…Urrunga et al analyzed OPTN data for adults with acute liver failure (ALF) who were listed for liver transplantation as Status 1 or 1A and underwent LDLT (N = 21) or DDLT (N = 2316) between October 1987 and April 2011. They found no strong evidence that the unadjusted survival probabilities for adults with ALF who underwent LDLT were inferior to those who underwent DDLT (29), and recent reports from Japan and Korea demonstrate patient survival exceeding 70% for ALF (30, 31). Several reports from large centers have also shown acceptable outcomes in selected patients with higher MELD scores or renal insufficiency (3235).…”
Section: Discussionmentioning
confidence: 96%
“…Urrunga et al analyzed OPTN data for adults with acute liver failure (ALF) who were listed for liver transplantation as Status 1 or 1A and underwent LDLT (N = 21) or DDLT (N = 2316) between October 1987 and April 2011. They found no strong evidence that the unadjusted survival probabilities for adults with ALF who underwent LDLT were inferior to those who underwent DDLT (29), and recent reports from Japan and Korea demonstrate patient survival exceeding 70% for ALF (30, 31). Several reports from large centers have also shown acceptable outcomes in selected patients with higher MELD scores or renal insufficiency (3235).…”
Section: Discussionmentioning
confidence: 96%
“…Liver transplantation is the treatment of choice for end-stage liver diseases[ 10 , 13 ]. In 2017, around 8000 patients all over the United State suffered from end-stage liver disease receiving liver transplantation and the number trends to increase 3% to 5% annually in the past 20 years along with the excellent outcomes with almost 95% survival rate at 1-year post-procedure and some patients could live even more than 30 years after liver transplantation[ 14 - 17 ]. Recent advances in basic and clinical sciences, including surgical technique, immunosuppressive therapy and postoperative supportive care, have led to the substantial improvement in quality of life and survival after liver transplantation[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified vasopressor requirement, estimated glomerular filtration rate, serum sodium concentration, recipient age, and donor age as significant predictors of transplant outcome . In a study from the United states, Urrunaga et al . compared LDLT (n=21) to DDLT (n=2316) for ALF and 1‐ and 5‐year survival probabilities were both 71% for LDLT and 79% for DDLT.…”
Section: Discussionmentioning
confidence: 99%
“…Among LDLT patients, cumulative patient survival rates at 1, 5, and 10 years were 79%, 74%, and 73%. 15 Kaido et al 16 18 In a study from the United states, Urrunaga et al 19 compared LDLT (n=21) to DDLT (n=2316) for ALF and 1-and 5-year survival probabilities were both 71% for LDLT and 79% for DDLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation